A Survey on Peroxide Content and Acidity level of Persian Doughnuts (Zoolbia and Bamieh) in Lorestan Province, West of Iran - Abdolrahim Kazemi Vardanjani (Journal of Global Pharma Technology, 2016)
Introduction: There are different chemical food contamination that causes detrimental effects on human health. For example, presence of peroxide in fried foods causes free radical formation. Free radicals are not only responsible for food spoilage, but also cause damage to body tissues and cancer, inflammatory diseases, atherosclerosis, aging and so on. The aim of this study was to evaluate the peroxide content and acidity level in Zoolbia and Bamiehin Lorestan province, West of Iran.Materials and Methods: 120 samples of Zoolbia and Bamieh doughnuts were purchased of Lorestan province distribution centers, during March 2014 to March 2015 and handled to Laboratory for chemical analysis and determination of their peroxide value and acidity.Results: present descriptive study results showed 56.92 and 43.07 % of the samples were out of standard limit and not suitable for consumption due to high levels of peroxides and acidity, respectively. The lowest and highest peroxide value were 1.1 and 2.9 mEq/kg, respectively. The minimum and maximum acidity of the samples were 0.7 and 2.9 wt%, respectively.Conclusion: Obtained results showed high peroxide contents in Persian doughnuts in Lorestan province than standard limit.Therefore, it seems educational programs about nutrition and using proper method for cooking and frying of foods is necessary. Continuous planning and surveillance, providing practical solutions by health authorities and regulatory organs, training of food staffs, using oils a few times and especial for food frying are recommended to reduce the peroxide content in Persian doughnuts (Zoolbia and Bamieh). Keywords: Zombie and Balmier, Acidity, Peroxide, Lorestan province, Iran